Germany : Financial Sector Assessment Program-Technical Note-Stress Testing, Interconnectedness, and Risk Analysis. (IMF Staff Country Reports; Country Report, 2022)
The financial sector weathered COVID relatively well on the back of high pre-crisis capital and liquidity buffers, strong public and private sector balance sheets, and unprecedented public and ECB support. Immediate risks to Germany's financial stability of Russia's invasion of Ukraine appear to be manageable due to the banks' limited direct exposures to Russia. However, risks associated with the economic fallout could impact some individual financial institutions, non-performing loans, and house prices. Real GDP growth was projected to regain momentum from mid-2022 onwards, but the war could hinder the recovery through supply constraints, higher-than-expected above-target inflation (with higher energy prices and supply constraints), a tightening of financial conditions, and shifts in investors' confidence.